Women and political participation in Katsina Local Government, Nigeria - Ibrahim Yusuf, Aisha (2015)
In Katsina local government area, women constitute almost half of the population. However despite their numerical significance, previous studies have shown that women there do not actively participate in political activities in the area. Since the creation of the local government area in 1987 to date no woman has ever occupied any elective position. This low representation of women in the local government presents a troubling issue to women as majority of victims of many unaddressed problems such as poverty,unemployment and illiteracy are women. In line with this argument therefore, this study aimed to investigate the reasons why women do not actively participate in politics and political activities in Katsina local government. Based on a review of literature and also application of a proposed method of civic voluntarism model, four research objectives and several hypotheses were generated in other to determine how key variables; income,time, civic skills, political interest, political efficacy, political knowledge, party identification, recruitment, cultural beliefs and religious beliefs from the proposed model affect women political participation. Using quantitative method, a questionnaire was administered to 402 women who were randomly selected from 12 different wards in Katsina local government. The result of the study found that about 58.7% of variance in political participation was explained by all the predictor variables. The study found the following variables: income, civic skills,political interest, party identification, recruitment, cultural beliefs and religious beliefs to be significant in predicting the likelihood for women to participate in political activities. However, political efficacy, political knowledge and time appeared to have no significant influence on political participation. The study also found that there is a difference between hours women spent on domestic work and on political participation and also differences between family monthly income among women and their level of political participation. Based on the above findings the researcher recommended that government should make concerted efforts in ensuring that there is dramatic increase in terms of female literacy rate this will aid in boosting their sense of psychological engagement with politics.